Pembinaan Karakter Santri melalui Latihan Pidato (Muhadhoroh) di Pondok Pesantren Modern Darussalam Bekasi - Muhammad Jundullah; Tajuddin Nur; Yayat Herdiana (ISLAMIKA, 2022)
This study aims to determine the efforts of educators in the process of fostering the character of students through speech training activities at the modern Darussalam Islamic boarding school. how the values of commendable characters affect the students and find out the various kinds of characters that develop and are formed in speech practice activities. The type of research used is qualitative, with the research subjects being teachers and students of the Darussalam Islamic boarding school, Bekasi. Data collection techniques in this study were observation, interviews and documentation. Data analysis uses data collection, data reduction, data presentation and drawing conclusions. The results of this study can show that speech training activities are able to provide optimal character development to students with discipline, responsibility, courage and ukhuwah Islamiyah. The values ​​that are internalized in this character building effort are religious values, independence, responsibility, discipline, self-confidence and respect for achievement. Efforts to build character through speech exercises are able to have a very good and positive impact on the personality of students and are welcomed by parents in seeking the best education for their children.